How to Solve the Problem in Physics (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the recommendations and methods of problem solving in physics and how problem solving affects the student. It is also important to keep the theoretical knowledge in the student's memory for a long time and use the analogy method to easily solve problems.